Using a partial atomic model from medium‐resolution cryo‐EM to solve a large crystal structure. Issue 1 (17th December 2020) - Fàbrega-Ferrer, Montserrat; Cuervo, Ana; Fernández, Francisco J.; Machón, Cristina; Pérez-Luque, Rosa; Pous, Joan; Vega, M. Cristina; Carrascosa, José L.; Coll, Miquel
Abstract : A partial 30% atomic model from a 7.8 Å resolution cryo‐EM volume was used to phase X‐ray data by molecular replacement. Abstract : Medium‐resolution cryo‐electron microscopy maps, in particular when they include a significant number of α‐helices, may allow the building of partial models that are useful for molecular‐replacement searches in large crystallographic structures when the structures of homologs are not available and experimental phasing has failed. Here, as an example, the solution of the structure of a bacteriophage portal using a partial 30% model built into a 7.8 Å resolution cryo‐EM map is shown. Inspection of the self‐rotation function allowed the correct oligomerization state to be determined, and density‐modification procedures using rotation matrices and a mask based on the cryo‐EM structure were critical for solving the structure. A workflow is described that may be applicable to similar cases and this strategy is compared with direct use of the cryo‐EM map for molecular replacement.